Entertainment-Education Behind the Scenes Case Studies for Theory and Practice - Frank, Lauren B.; Falzone, Paul.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This Open Access book tracks the latest trends in the theory, research, and practice of entertainment-education, the field of communication that incorporates social change messaging into entertaining media. Sometimes called edutainment, social impact television, narrative persuasion, or cultural strategy, this approach to social and behavior change communication offers new opportunities including transmedia and digital formats. However, making media can be a chaotic process. The realities of working in the field and the rigid structures of scholarly evaluation often act as barriers to honest accounts of entertainment-education practice. In this collection of essays, experienced practitioners offer unique insight into how entertainment-education works and present a balanced view of its potential pitfalls. This book gives readers an opportunity to learn from the successes and mistakes of the experts, taking a behind-the-scenes look at the business of making entertainment-educationmedia.
Part I . From Then to Now: Historical Perspectives -- 1. Introduction: Entertainment-Education Behind the Scenes -- 2. Miguel Sabido$1 (Bs Entertainment-Education -- 3. The Impact of Social Change Communication: Lessons Learned from Decades of Media Outreach -- 4. Entertainment-Education as Social Justice Activism in the United States: Narrative Strategy in the Participatory Media Era -- 5. A Strange Kind of Marriage: The Challenging Journey of Entertainment-Education Collaboration -- Part II . From Theory to Practice -- 6. Transportation into Narrative Worlds -- 7. The Emotional Flow Hypothesis in Entertainment-Education Narratives: Theory, Empirical Evidence, and Open Questions -- 8. Music and Culture in Entertainment-Education -- 9. Strengthening Integration of Communication Theory into Entertainment-Education Practice: Reflections from the La Peor Novela Case Study -- Part III. From Research to Impact -- 10. Using Audience Research to Understand and Refine a Radio Dramain Myanmar Tackling Social Cohesion -- 11. Social Norms Theory and Measurement in Entertainment-Education: Insights from Case Studies in Four Countries -- 12. In Search of Entertainment-Education$1 (Bs Effects on Attitudes and Behaviors -- 13. When Life Gives You Lemons: What to Do When Something Goes Wrong in Your Carefully Planned Research and How to Avoid Disasters in the First Place -- 14. Mind the Gap! Confronting the Challenges of Translational Communication Research in Entertainment-Education -- Part IV . From Concept to Implementation -- 15. Entertainment-Education, American Style: Informing and Studying Hollywood$1 (Bs Portrayals of Social Issues -- 16. Challenging the Forcefield: Crafting Entertainment-Education Transmedia Campaigns -- 17. Youth and Entertainment-Education -- 18. How to Make a Living Legend: Bibliobandido as Literacy Movement Building -- 19. When Your Audience Is Your Channel: Facebook for Behavior Change -- 20. Last Mile Media: A How-To Guide -- 21. Epilogue: The Next Reel for Entertainment-Education.s
Keywords: Communication in economic development; Communication in medicine; Development Communication; Health Communication